Clinical aspects of breastfeeding (New York Hayle Medical, 2023)
Lactation is a process of milk secretion by the mammary glands in female mammals including humans. Breastfeeding refers to the action of feeding milk from the breast of a lactating female to a young child or a new born baby. Breastfeeding is helpful in reducing risk of several diseases including type-1 diabetes, asthma, childhood leukemia, allergies and obesity. Benefits of breastfeeding for the mother in the long term include reduced risk of rheumatoid arthritis, breast cancer, metabolic syndrome, cardiovascular disease, and diabetes. Some of the common problems associated with lactation include sore nipples, breast engorgement, too little or too much breast milk, and mastitis. This book on breastfeeding presents researches and studies performed by experts across the globe. It will also provide interesting topics for research which interested readers can take up. The extensive content of this book provides the readers with a thorough understanding of the subject.
Keywords: Breastfeeding; Breast milk; Infant- nutrition; Lactation- Nutritional aspects; Watts, Johanna ed